Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials. (1st July 2023) - Li, Qing-Lin; Shan, Rui; Wang, Shu-Xiao; Yuan, Hao-Ran; Chen, Yong
Highlights: Different supports Ni-based catalyst was prepared for polyethylene pyrolysis. The Ni/Al2 O3 show excellent selectivity for carbon nanomaterials (36.5%). The carbon nanotubes have high purity and graphitization degree. The Ni/Al2 O3 had abundant pore structure and moderate MSI. More fishbone like carbon nanofibers were obtained from Ni/TiO2 . Abstract: To understand the influence of support materials on the reactivity of catalysts, four nickel- based catalysts supported on different materials (ZrO2, TiO2, Nb2 O5, and Al2 O3 ) were developed and investigated in the carbon nanotubes production from catalytic pyrolysis of polyethylene using two-stage fixed bed reactor. The results showed that the Ni/Al2 O3 catalyst generated the highest carbon material yield of 36.5 wt%, while the order of carbon material yield was Ni/Al2 O3  > Ni/TiO2  > Ni/ZrO2  > Ni/Nb2 O5 . To explore the correlation between catalysts properties and carbon products, the essential structural characteristics of fresh catalyst and reacted catalyst were analyzed by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (TEM), temperature program oxidation (TPO), nitrogen adsorption measurements and Raman spectroscopy. The Ni/Al2 O3 catalyst with the highest surface area, abundant pore structure, and moderate metal-support interaction promoted the decomposition of pyrolysis volatiles to produce carbon nanomaterials, which were consist of carbon nanotubes (CNTs). CNTs are the main component of carbon materials produced, accounting for a relatively high proportion. In comparison, the large metal active particles and weak metal-support interaction of Ni/TiO2 catalyst had a negative impact on the formation of CNTs, generating many fishbone like carbon nanofibers (CNFs). Moreover, the poor pore structure and larger metal active particles for Ni/ZrO2 and Ni/Nb2 O5 catalyst led to a low carbon deposition yield and poor quality of CNTs. The results provide valuable data and theoretical support for the research on the preparation of valuable carbon nanotubes from waste plastics.